Extending the shelf life of soft cheese using nanoencapsulation - Al-Mowsowy, Azhar Jawad; salih, Firas Ahmed (Journal of Kerbala for Agricultural Sciences, 2023)
The study conducted to use the encapsulation of Nigella sativa oil to increase its thermal stability and making it more resistant to oxidation, lipolysis and use it to enrich soft cheese. Nigella Sativa oil particles was prepared by encapsulating oil with chitosan nanoparticles (NSP) by using the ionotropic gelation technique. The prepared size of the nanoparticles was 70.93 nm. This study included Four treatments to produce soft cheese. In the 1st treatment(M1) 0.5% of the solution was added to NSP particle pasteurized milk (m1), while the 2th treatment(M2) treatment 1% of liquid solutions to NSP was added to pasteurized milk. A 0.5% and 1% of liquid solutions NSP were added to cared treatments (M3 and M4), respectively. The 5th treatment (M5), the soft cheese was used as a control and left without additions. All treatments were kept in cooling at a temperature of 7 ± 2o C for 14 days for conduct the physiochemical and microbiological examinations. The results showed that the coating of Nigella sativa oil with chitosan and in the nano capsulate form increase the resistance of this oil to the manufacturing conditions, which led to an increase in its resistance to heat and oxidation processes. Also, the addition of nanoparticles to soft cheese in two percentages 0.5 & 1% caused increase the preservation ability of cheese during the 14 days of cooling storage.